2001
DOI: 10.1093/ps/80.6.741
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Enrichment of Chicken Meat. 1. Use of Very Long-Chain Fatty Acids in Chicken Diets and Their Influence on Meat Quality: Fish Oil

Abstract: We assessed the effect of a diet supplemented with fish oil (FO) on the performance, fatty acid (FA) composition, quality, and sensory traits of broiler meat. Diets enriched with 0, 2, or 4% FO plus tallow (T) up to 8% added fat (T1, T2, and T3, respectively) were given to the birds throughout a 38-d growth period. T3 was replaced by a mixture of FO, linseed oil (LO), and T (1, 3, and 4% respectively) for 1 wk (T4) or 2 wk (T5) before slaughter. Meat quality, taste, and FA profile were determined. Higher final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
102
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(122 citation statements)
references
References 30 publications
14
102
1
3
Order By: Relevance
“…The fatty acid profile of meat could be altered by adding fish products to the feed for broilers (López-Ferrer et al, 2001a;Cortinas et al, 2004) or vegetable oils (López-Ferrer et al, 2001b;Schneiderova et al, 2007;Zelenka et al, 2008). Similar findings were detected in the present study (Table 3).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fatty acid profile of meat could be altered by adding fish products to the feed for broilers (López-Ferrer et al, 2001a;Cortinas et al, 2004) or vegetable oils (López-Ferrer et al, 2001b;Schneiderova et al, 2007;Zelenka et al, 2008). Similar findings were detected in the present study (Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…to the diet. It has been shown that the content of n-3 PUFA, particularly of α-linolenic acid (ALA,, in poultry meat can readily be improved by increasing the levels of n-3 PUFA in poultry diets through the incorporation of vegetable oils (López-Ferrer et al, 2001b;Schneiderova et al, 2007;Zelenka et al, 2008) or oily fish by-products (López-Ferrer et al, 2001a;Cortinas et al, 2004). However, some authors reported the unpleasant flavour of fish in the meat of broilers fed 1.5% to 2.5% of FO (Hardin et al, 1964).…”
mentioning
confidence: 99%
“…Indeed, our study indicated that birds fed the diet supplemented with MA had a lower concentration of SFA but higher PUFA and n-3 fatty acid concentration, indicating the consumption of this meat could reduce the risk of diseases such as CHD. Similar results were also observed by Lo´pez-Ferrer et al (1999, 2001, who also reported an increased USFA concentration with v-3 fatty acid-enriched fish oil.…”
Section: Fatty Acid Composition Of Breast Meatsupporting
confidence: 89%
“…Despite the known benefits of diets with better profiles of PUFA omega 3, the supplementation of broiler diets with these sources cannot be viable due to the high cost, lack of availability, and the sensorial and organoleptic effects associated with lipid oxidation (Lopez-Ferrer et al, 2001).…”
mentioning
confidence: 99%